An Integrated Strategy for Investigating Antioxidants from Ribes himalense Royle ex Decne and Their Potential Target Proteins - Chuang Liu; Yuqing Lei; Youyi Liu; Jingrou Guo; Xingyi Chen; Yifei Tang; Jun Dang; Minchen Wu (MDPI AG, 2023)
Natural products have been used extensively around the world for many years as therapeutic, prophylactic, and health-promotive agents. Ribes himalense Royle ex Decne, a plant used in traditional Tibetan medicine, has been demonstrated to have significant antioxidant and anti-inflammatory properties. However, the material basis of its medicinal effects has not been sufficiently explored. In this study, we established an integrated strategy by online HPLC-1,1-diphenyl-2-picrylhydrazyl, medium-pressure liquid chromatography, and HPLC to achieve online detection and separation of antioxidants in Ribes himalense extracts. Finally, four antioxidants with quercetin as the parent nucleus were obtained, namely, Quercetin-3-O-β-D-glucopyranoside-7-O-α-L-rhamnopyranoside, Quercetin-3-O-β-D-xylopyranosyl(1-2)-β-D-glucopyranoside, Quercetin-3-O-β-D-glucopyranoside, and Quercetin-3-O-β-D-galactoside. Until now, the four antioxidants in Ribes himalense have not been reported in other literatures. Meanwhile, the free-radical-scavenging ability of them was evaluated by DPPH assay, and potential antioxidant target proteins were explored using molecular docking. In conclusion, this research provides insights into the active compounds in Ribes himalense which will facilitate the advancement of deeper studies on it. Moreover, such an integrated chromatographic strategy could be a strong driver for more efficient and scientific use of other natural products in the food and pharmaceutical industries.